Advances in bio-based fiber : moving towards a green society - Rangappa, Sanjay Mavinkere; Madhu, P.; Parameswaranpillai, Jyotishkumar; Siengchin, Suchart; Gorbatyuk, Sergey (Woodhead Publishing, 2021)
"Advances in Bio-Based Fibres: Moving Towards a Green Society describes many novel natural fibers, their specific synthesis and characterization methods, their environmental sustainability values, their compatibility with polymer composites, and a wide range of innovative commercial engineering applications. As bio-based fiber polymer composites possess excellent mechanical, electrical and thermal properties, along with highly sustainable properties, they are an important technology for manufacturers and materials scientists seeking to improve the sustainability of their industries. This cutting-edge book draws on the latest industry practice and academic research to provide advice on technologies with applications in industries, including packaging, automotive, aerospace, biomedical and structural engineering. Provides technical data on advanced material properties, including electrical and rheological Gives a comprehensive guide to appraising and applying this technology to improve sustainability, including lifecycle assessment and recyclability Includes advice on the latest modeling techniques for designing with these materials."--